Increasing Adolescent Reproductive Health Awareness through Role Play Drama Method - Rahmadhani, Wulan; Mutoharoh, Siti; Kusumastuti, Kusumastuti; Dewi, Adinda Putri Sari (Prosiding University Research Colloquium, 2022)
Adolescents are faced with complex problems related to physical, psychological and emotional changes that caused with them experience health problems. Lack of knowledge, would had an impact on reproductive health status. Availability of adolescent care health services that can meet adolescent health needs, especially adolescent-friendly reproductive health services. The purpose of this activity was to increased understanding and awareness of health among adolescents. The method used was the planning stage and the implementation stage. In this community service, the participants played a drama that has been arranged by the service team. This drama told about an incident that is currently happening a lot among adolescents, namely free sex behavior. Adolescents who taken a part in this activity understood the purpose of this activity, and adolescents could hold the material that has been given by the implementing team.